O estilo em Como se Deve Escrever a História, de Luciano (Nuntius Antiquus, 2013)
Although mixed, The way to write history is a document written mostly in middle style. Even though Lucian uses metaphors in the letter to Philo among other tropes and figures, comparison is one of the style resources most present in the text, maybe the main resource used. Not all cases of comparison used in The way to write history were presented, but when discussing some of them it is considered that comparison is a characteristic resource of the style Lucian uses. That is, according to the decorum of a treatise-moral demonstrative-deliberative letter of the vituperative kind. In order to make the text effective, the didactic and vice correcting functions demand imitation ways using a middle/ low style.